Taking on technocracy : nuclear power in Germany, 1945 to the present - Augustine, Dolores L. (Protest, culture and society, 2018)
The German abandonment of nuclear power represents one of the most successful popular revolts against technocratic thinking in modern times'the triumph of a dynamic social movement, encompassing a broad swath of West Germans as well as East German dissident circles, over political, economic, and scientific elites. Taking on Technocracy gives a brisk account of this dramatic historical moment, showing how the popularization of scientific knowledge fostered new understandings of technological risk. Combining analyses of social history, popular culture, social movement theory, and histories of science and technology, it offers a compelling narrative of a key episode in the recent history of popular resistance.